Effects Of Titania Additive On Phases Development And Hardness Of Spark Plasma Sintered Mullite-Carbon-MNO2 Ceramic Composite - Aramide, F.O.; Popoola, A.P.I. (Ife Journal of Technology, 2019)
Effects of varied contents of titania on the phase development and properties of spark plasma sintered (SPS) mullite-carbon- MnO2 ceramic composite was investigated. The raw materials used were kaolin clay, graphite, manganese oxide and titania. Samples were prepared by blending pre-calculated amounts of raw materials in Turbular mixer at a speed of 72 rev/min. The homogenous mixture were sintered in the SPS machine at 1000°C at a sintering pressure of 40 MPa, heating rate of 50°C/min and holding time of 10 min in a graphite die of 20mm. The phases in the sintered samples were characterized using x-ray diffractometry analysis (XRD). Microstructure of the samples were examined using scanning electron microscope (SEM). Harness of the sintered samples was also investigated using Vickers hardness tester. It was observed that the phases evolved in the sample were influenced by titania content. The presence of Mn2O3 in the sample lead to formation of silimanite in preference to mullite when sintered 1000°C. 12% titania in sample D aided development of mullite phases within the sample. Presence of 16% titania and Mn2O3 led to development of carbides like Al4C3 and Al4Si2C5 in sample E. Addition of titania to the samples progressively improved on densification of the samples with increased titania contents. It was concluded that the development of carbides within the ceramic matrix is responsible for the increased hardness of the sample.